Effect of irrigation on rural transformation and income at the district level in Bangladesh - Subrata Saha; Mohammad Jahangir Alam; Al Amin Al Abbasi; Ismat Ara Begum; Maria Fay Rola-Rubzen; Panam Parikh; Andrew M. McKenzie (PLoS ONE, 2025)
The study assesses the effect of investment in irrigation on rural transformation (RT) and rural income in Bangladesh. The analysis utilizes panel data from four rounds of nationally representative Household Income and Expenditure Surveys from 2000 to 2016. The share of irrigated land serves as an indicator of the level of irrigation investment in irrigation infrastructure. The study employs both ordinary least squares and fixed effects regression models. The findings indicate that the share of irrigated land has a positive effect on RT, particularly on the share of high-value agriculture and the share of rural non-farm employment. Additionally, the share of irrigated land positively affects rural income. Moreover, the study reveals that the effect of irrigation is positive at all stages of RT, especially for the share of high-value agricultural commodities. However, the impact of irrigation on the share of rural non-farm employment and rural income is inconclusive across different stages of RT. Overall, our results underscore the importance of prioritizing the construction of irrigation infrastructure by the government and encouraging the private sector to invest in irrigation.